Distribution and Drift of Commercial Fish Larvae in the Barents Sea in June-July 1967 G (Raspredelenie i Dreif Lichinok Promyslovykh Ryb Barentseva Morya v Iyune-Iyule 1967 G) - Baranekova,A. S.; Zhuravleva,V. K.; Khokhlina,N. S. (1973)
The distribution of fish eggs and larva was studied by trawling a standard roe net and a ringtrawl. Capelin and ocean perch larvae predominated in the catches, whereas American plaice and smallhead flounder eggs were the most abundant of that form. In the region investigated the quantity of larvae collected exceeded that caught in both 1965 and 1966. (Author) Trans. of Materialy Rybokhozyaistvennykh Issledovanii Servernogo Basseina (USSR) v14 p26-43 1970, by V. Astvazaturov.